2020
DOI: 10.1364/ome.389740
|View full text |Cite
|
Sign up to set email alerts
|

Robust simultaneous multiwavelength bulk laser based on Yb:LaMgB5O10 crystal: from continuous wave to ultrashort pulses

Abstract: We present a robust simultaneous multiwavelength bulk laser based on Yb:LaMgB5O10 (Yb:LMB) crystal, including its continuous-wave (CW) and ultrafast pulsed regimes. CW dual wavelengths at 1077 nm and 1091 nm with an average output power of 2.67 W were achieved with a 1% output coupling (OC). A maximum output power of 4.42 W with triple wavelengths of 1056, 1077, and 1091 nm was generated with 3% OC. In the case of 25% OC, the Yb:LMB laser can operate with four wavelengths (1025.1, 1031.4, 1033.2, and 1053.3 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Next to Nd, the Yb 3+ ion is also suitable for obtaining lasers with emission in the near infrared (NIR) region. [ 24 ] Based on the LaMgB 5 O 10 host, a 2.76 W CW laser output power was obtained at the absorbed pump power of 7.7 W with a slope efficiency of 64.5%. Yb:LMB lasers simultaneously oscillated at 1053 and 1057 nm, which indicated that it may have application in terahertz wave generation.…”
Section: Luminescent Mixed Borates Based On Rare Earthsmentioning
confidence: 99%
“…Next to Nd, the Yb 3+ ion is also suitable for obtaining lasers with emission in the near infrared (NIR) region. [ 24 ] Based on the LaMgB 5 O 10 host, a 2.76 W CW laser output power was obtained at the absorbed pump power of 7.7 W with a slope efficiency of 64.5%. Yb:LMB lasers simultaneously oscillated at 1053 and 1057 nm, which indicated that it may have application in terahertz wave generation.…”
Section: Luminescent Mixed Borates Based On Rare Earthsmentioning
confidence: 99%